2011
DOI: 10.1074/jbc.m110.204941
|View full text |Cite
|
Sign up to set email alerts
|

Arrestin-Rhodopsin Binding Stoichiometry in Isolated Rod Outer Segment Membranes Depends on the Percentage of Activated Receptors

Abstract: In the rod cell of the retina, arrestin is responsible for blocking signaling of the G-protein-coupled receptor rhodopsin. The general visual signal transduction model implies that arrestin must be able to interact with a single light-activated, phosphorylated rhodopsin molecule (Rho*P), as would be generated at physiologically relevant low light levels. However, the elongated bi-lobed structure of arrestin suggests that it might be able to accommodate two rhodopsin molecules. In this study, we directly addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 55 publications
5
48
1
1
Order By: Relevance
“…S6 and SI Materials and Methods). Therefore, we conclude that the DEER measurements apply to a high-affinity one-to-one arrestin- P-Rh* complex, consistent with the finding that regardless of the binding stoichiometry, arrestin-1 stabilizes the active state (metarhodopsin II) of only one rhodopsin (42). However, the data do not eliminate the possibility of complexes with other stoichiometry in the native disk membrane that do not alter arrestin conformation.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…S6 and SI Materials and Methods). Therefore, we conclude that the DEER measurements apply to a high-affinity one-to-one arrestin- P-Rh* complex, consistent with the finding that regardless of the binding stoichiometry, arrestin-1 stabilizes the active state (metarhodopsin II) of only one rhodopsin (42). However, the data do not eliminate the possibility of complexes with other stoichiometry in the native disk membrane that do not alter arrestin conformation.…”
supporting
confidence: 65%
“…In this case, a significant domain movement does not seem to be necessary. On the other hand, it may be that the N domain and finger-loop region are the primary sites of interaction with P-Rh* and that the C domain has an accessory function, including the possibility of interaction with another receptor molecule in an inactive state (42,43), the membrane surface, or other signaling proteins. Among the four vertebrate subtypes, arrestin-1 shows the highest receptor specificity and selectivity for P-Rh* (50).…”
mentioning
confidence: 99%
“…Principally, the reorganized interface could thus provide a secondary binding site for the accommodation of a GPCR dimer. Indeed it has been suggested that the arrestin C loop binds a second rhodopsin molecule in disc membranes containing high levels of activated rhodopsin (18,42). Site-directed spin-labeling studies, on the other hand, revealed a high flexibility of this arrestin region upon binding to both highly activated P-ROS* and nanodiscs containing only monomeric P-rhodopsin* (28).…”
Section: Resultsmentioning
confidence: 99%
“…Monomeric rhodopsin was shown to be necessary and sufficient for high-affinity arrestin-1 binding (26,45). However, recent reports suggest that two types of arrestin-1-rhodopsin complexes are formed upon activation of a high fraction of rhodopsin in native disk membranes, with 1:1 and 1:2 arrestin: rhodopsin stoichiometries (46,47). In the latter, arrestin-1 apparently binds only one rhodopsin with high affinity, stabilizing its Meta II state (46) and trapping all-transretinal (47), whereas the other molecule is engaged with much lower affinity by distinct arrestin-1 elements localized in the C-domain (47).…”
Section: Hmentioning
confidence: 99%
“…However, recent reports suggest that two types of arrestin-1-rhodopsin complexes are formed upon activation of a high fraction of rhodopsin in native disk membranes, with 1:1 and 1:2 arrestin: rhodopsin stoichiometries (46,47). In the latter, arrestin-1 apparently binds only one rhodopsin with high affinity, stabilizing its Meta II state (46) and trapping all-transretinal (47), whereas the other molecule is engaged with much lower affinity by distinct arrestin-1 elements localized in the C-domain (47). All forms of rhodopsin used here were solubilized by a large excess of bicelles and most of the perturbations were observed to be in the N domain of arrestin-1 and in the C terminus that is anchored to this part of the molecule (Figs.…”
Section: Hmentioning
confidence: 99%